ANALYSIS OF TAX PLANNING APPLICATION ON INCOME TAX ARTICLE 21 USING NET AND GROSS-UP METHODAS AN EFFICIENCY STRATEGY FOR COMPANY INCOME TAX (Case Study on PT. X, Bali) - WICAKSANA ABYUDA, GEDE SATYA (Jurnal Ilmiah Mahasiswa FEB, 2019)
Tax is a compulsory contribution to the country owed by an individual or entity that is compelling under thelaw. For the country, tax is an important source of revenue, however for an individual or entity, tax is a cost thatcan reduce their profits. This study aims to determine the efficiency of Company Income Tax through taxplanning on Income Tax Article 21, using the net method and the gross up method based on Law Number 36 of2008. The type of this research is replication with the differences in object and time of research. This research isa qualitative descriptive study with case study research approach, where describing the application of the netmethod and gross up method on Income Tax Article 21 and its implications for Company Income Tax. Thisstudy uses secondary data sources obtained directly from data sources, namely PT. X, Bali through interviewand documentation. The results of this study indicate that with appropriate tax planning and using the gross upmethods in the calculation of Income Tax Article 21, then utilizing the applicable rules and rates in accordancewith Law Number 36 of 2008 Article 17 and Article 31E, Company Income Tax is efficient with the amount ofIDR 17,149,313.Â